2022
DOI: 10.3390/w14030459
|View full text |Cite
|
Sign up to set email alerts
|

Identify Priority Control Pollutants and Areas of Groundwater in an Old Metropolitan Industrial Area—A Case Study of Putuo, Shanghai, China

Abstract: Industrial activities have raised widespread concerns about groundwater pollution and human health. Shanghai’s industrial land has been polluting the groundwater for more than 30 years; however, it is not clear whether it poses a risk to human health. This study explores the health risk degree in different groups of groundwater in old industrial areas in Shanghai, China. We selected eight heavy metal elements (As, Cd, Cr, Ni, Hg, Pb, Cu, and Zn) as the research objects and analyzed the characteristics of conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Peng et al [12] studied the health risks of heavy metals in industrial land, and found that Pb, Cd, Zn, Ni, and As had a higher risk. Yuan and Wang [13] studied the risk of heavy metals under two land types and found that the risk of industrial land was higher. The reason why the risk of heavy metals varies under different land-use types is that the sources of pollution are different.…”
Section: Introductionmentioning
confidence: 99%
“…Peng et al [12] studied the health risks of heavy metals in industrial land, and found that Pb, Cd, Zn, Ni, and As had a higher risk. Yuan and Wang [13] studied the risk of heavy metals under two land types and found that the risk of industrial land was higher. The reason why the risk of heavy metals varies under different land-use types is that the sources of pollution are different.…”
Section: Introductionmentioning
confidence: 99%